Níveis de investigação em oficinas oferecidas na Estação Ciências do Parque Tecnológico Itaipu Foz do Iguaçu - PR - Silva, Raquel Rodrigues Nunes da (2018)
The pertaining Station Sciences to the National Park of Itaipu, located in the city of Estuary of the Iguaçu, been of the Paraná. It can be characterized as a space of not formal education, in which students of the schools of the region West of the Paraná participate of didactic activities in the form of thematic workshops. Such workshops are organized by the team of the Station Sciences, having, as estimated, elements of Ensino for Inquiry. Ahead of a roll of workshops, the professors of the schools can choose interest subjects its students and set appointments the visit to the Station. It is in this context that this work if constituted and brings reflections on Ensino for Inquiry, in the perspective to identify to which the inquiry level that the activities carried through in the Station Sciences - PTI promote for the students, during the participation in workshops. The theoretical support of Banchi and Bell, in allowed them to characterize the investigativas activities in four different levels and Sasseron and Carvalho in them indicate important elements of education for inquiry, as a valuable boarding in the promotion of the Scientific Alfabetização. One is about a qualitative research, in which, for the register of the comments, we use the video writing of a subject presented to the students during gone of them to the Station Sciences. A Subject is constituted by three workshops in circuit form, in which each one of the workshops complements to another one, as well as each one it contributes to present and to argue the general subject. We select for this study the workshop “composed Solar Light” for three workshops: “Because the sky is blue”, “As the heat is imprisoned in the Land”, “What it is solar radiation”. Ahead of the analyses carried through in this research, we can indicate that the workshops offered in the Station Sciences, can be characterized in two levels, being Structuralized Inquiry and Inquiry of Confirmation. In the first case, the pupils receive the questions and the procedures, but the collected data take off its proper conclusions on the basis of. In as in case that, Inquiry of Confirmation, the students previously confirm the material presented by the monitor. Of ownership of the result, we understand that the workshops of the Station Sciences must be revised, in the direction more to make possible to the students raised levels of inquiry. However, she is necessary to ponder on the difficulty to insert the students in a investigativo thought in short space of time, as the offered one to the students from the development of workshops for the understanding of a specific subject.